Semi‐natural habitats mitigate the effects of temperature rise on wild bees. Issue 2 (26th August 2016) - Papanikolaou, Alexandra D.; Kühn, Ingolf; Frenzel, Mark; Schweiger, Oliver
Summary: The effect of climate change on wild bee communities is of major concern since the decline of bee species could imperil the provision of pollination services. Additionally, habitat loss and fragmentation are major threats to wild bee populations, but improvements to the landscape structure could also improve the general conditions for wild bees. However, potential interactive effects of climate change and landscape structure on wild bee communities remain unknown. In this study, we assessed the potential of semi‐natural areas to maintain robust communities under changing weather conditions. We used bee monitoring data from six 4 × 4 km field sites across Germany. Almost 30 000 bee specimens were collected from 2010 to 2012 in 16 local communities per site at six sampling occasions per year. Following a multimodel inference approach, we identified the most important weather and landscape variables as well as interaction terms that affect wild bee species richness and total abundance. Correcting for overall phenology, we found a strong negative relationship between bee species richness and temperature, indicating that future increasing temperatures will lead to a decrease in species richness. However, a high proportion of semi‐natural habitats can considerably decrease the detrimental effect of warmer temperatures on bee species richness and abundance. Synthesis and applications . Semi‐natural areas and green infrastructure elements within agricultural landscapes become even more important under changing temperature conditions to mitigate the negative effects of increasing temperatures on wild bee species richness and total abundance. This has important implications for conservation decision making, suggesting that maintaining or restoring a fair amount of semi‐natural areas could serve as a countermeasure against climate change for wild bees.